Cutaneous synergistic analgesia of bupivacaine in combination with dopamine in rats. (4th May 2016) - Tzeng, Jann-Inn; Wang, Jieh-Neng; Wang, Jhi-Joung; Chen, Yu-Wen; Hung, Ching-Hsia
Highlights: Dopamine produced dose-dependent cutaneous analgesia. Dopamine was less potent than bupivacaine at producing cutaneous analgesia. Dopamine elicited a similar duration of cutaneous analgesia compared with bupivacaine. Dopamine combined with bupivacaine produced a synergistic analgesic effect. Abstract: The main goal of the study was to investigate the interaction between bupivacaine and dopamine on local analgesia. After the blockade of the cutaneous trunci muscle reflex (CTMR) responses, which occurred following the drugs were subcutaneously injected in rats, the cutaneous analgesic effect of dopamine in a dosage-dependent fashion was compared to that of bupivacaine. Drug-drug interactions were evaluated by isobolographic methods. We showed the dose-dependent effects of dopamine on infiltrative cutaneous analgesia. On the 50% effective dose (ED50 ) basis, the rank of drug potency was bupivacaine (1.99 [1.92–2.09] μmol/kg) greater than dopamine (190 [181–203] μmol/kg) ( P  < 0.01). At the equianalgesic doses (ED25, ED50, and ED75 ), dopamine elicited a similar duration of cutaneous analgesia compared with bupivacaine. The addition of dopamine to the bupivacaine solution exhibited a synergistic effect. Our pre-clinical data showed that dopamine produced a dose-dependent effect in producing cutaneous analgesia. When compared with bupivacaine, dopamine produced a lesser potency with a similar duration of cutaneous analgesia. Dopamine added to the bupivacaine preparation resulted in a synergistic analgesic effect.